The Urgency of Presidential Policy to Revitalize and Maintain the Existence of Cooperatives Based on Pancasila - Seno Wibowo Gumbira; I Gusti Ayu Ketut Rachmi Handayani; Kukuh Tejomurti Tedjomurti (Sriwijaya Law Review, 2019)
The article aims to examines how the role of the President of the Republic of Indonesia as the head of state as well as the head of government through its policies and legal products. It is because the President has a role in creating a conducive atmosphere in the economic sector especially in revitalizing and maintaining the existence of a Cooperative as Indonesia's economic pillar based on Pancasila to face the wave of the liberal economy in the era of globalization. This situation occurs, perhaps, due to the lack of confidence and understanding of the Pancasila as a social philosophy. This problem can be observed by several phenomena occurring in the community such as the malignant and violent settlement of problems resolution in a social, political, cultural, legal, and religious system. This study applies normative methods with a statute approach. As a result, it can be concluded that a legal product comes from the 1945 Constitution to the Presidential legal products, namely government regulation and presidential instruction will have an implication to the objective and the result whether it is good or bad.